Comparative analysis of immunohistochemistry and flow cytometry in the diagnosis of acute leukaemia: a single centre study - Sarma, Usha; Bhattacharyya, Jina; Hazarika, Ekaparna (International Journal of Research in Medical Sciences, 2023)
Background: Morphological evaluation and immunophenotyping are the major diagnostic modalities of acute leukaemia (AL). Although immunohistochemistry (IHC) and flow cytometry (FCM) are necessary for lineage assessment, but in many cases the use of these modalities alone might possess a diagnostic challenge. The study was aimed to analyse the diagnostic utility of IHC and FCM in the diagnosis of AL. Methods: This cross-sectional hospital-based study was done for one year and included 55 cases. Following peripheral blood examination and bone marrow study, IHC and FCM analysis was done using CD34, anti-MPO, CD3 and CD20. Results: There were 74.5% acute myeloid leukaemia (AML) and 25.5% acute lymphoblastic leukaemia (ALL) cases. By IHC, CD34 was positive in 94.5% cases, anti-MPO in 69.1%, CD3 in 3.6% and CD20 in 12.7% cases. But by FCM, CD34 was positive in 96.2% cases, anti-MPO in 61.5%, CD3 in 3.8% and CD20 in 19.3% cases. FCM could not be done for 3 cases as there was dry tap with pancytopenia and lineage assessment was done by IHC. On comparative analysis, CD34 was found to be better expressed by FCM. Anti-MPO and CD20 were better expressed by IHC and CD3 was equally expressed by both. Conclusions: IHC is an easy and cost-effective technique which gives an accurate characterization of the lineage and subtype of AL, especially in cases where use of FCM is limited such as cases with dry tap and pancytopenia and in limited resource centers.